IMPLEMENTASI PERATURAN WALIKOTA PAREPARE NO. 7 TAHUN 2018 TENTANG EFEKTIVITAS AKUNTABILITAS PENGELOLAAN ZAKAT DI BAZNAS PAREPARE - Sarmila, Sarmila; Mahsyar, Mahsyar; Muliati, Muliati; Semaun, Syahriyah; Musyarif, Musyarif (Jurnal Istiqro, 2024)
This thesis discusses the implementation of Parepare City Regulation No. 7 of 2018 regarding the effectiveness of accountability in zakat management at BAZNAS Parepare. The purpose of this research is to determine the implementation of Mayor Regulation No. 7 of 2018 on the effectiveness and accountability of zakat management at the National Amil Zakat Agency (BAZNAS) in Parepare City. The research method used is qualitative research with a field research design. The number of informants in this study was 3 people from BAZNAS, and the data collection techniques included observation, interviews, and documentation. Data analysis employed data reduction, presentation, and conclusion drawing. The results of this research indicate that: 1) The implementation of Mayor Regulation No. 7 of 2018 on zakat management at BAZNAS Parepare has been carried out well in accordance with legal provisions for zakat management. BAZNAS has demonstrated commitment to accountability and transparency by integrating open reporting mechanisms that are easily accessible and comply with Sharia principles. 2) The effectiveness of zakat management at BAZNAS Parepare shows effective management, as evidenced by an open and easily accessible reporting system for the public, and BAZNAS's ability to ensure that zakat funds are distributed appropriately in accordance with Sharia principles and community needs. 3) Accountability in zakat management at BAZNAS Parepare indicates that BAZNAS Parepare has shown a high level of accountability in zakat management. The independent audit process validates BAZNAS's performance in ensuring compliance with accounting standards and Sharia provisions, demonstrating BAZNAS's seriousness in maintaining transparency and integrity, and making zakat management responsive to community needs